Plasminogen activator inhibitor-1 polymorphisms as a risk factor for chronic periodontitis in North Indian population - Puja Debnath; Jayant Dewangan; Divya Tandon; Vivek Govila; Mona Sharma; Virendra Kumar; Smita Govila; Srikanta Kumar Rath (Journal of Oral Biology and Craniofacial Research)
Objectives: Impaired plasminogen activator inhibitor-1 (PAI-1), controlling coagulation and the fibrinolytic system is supposed to be involved in the pathogenesis of periodontitis. This study was performed to examine the association of PAI-1 gene polymorphisms with Chronic Periodontitis (CP) and alveolar bone loss severity involved with the disease and for understanding the role of genetic contributions in disease progression. Methods: 87 volunteers were included in the study. Genomic DNA was isolated from peripheral blood, subsequently, DNA samples were subjected to polymerase chain reaction and endonuclease digestion. Direct gene sequencing were performed for all the samples to identify genotype polymorphisms (rs 11560324) in the 3’ untranslated region of PAI-1 gene. For bone loss assessment full mouth IOPA was taken. Results: Statistical analysis showed that for SNP PAI-I in 3’ UTR, genotype CC (homozygous mutant) and allele C (mutant) has a risk associated with CP, although statistically significant association was not found. An increased risk of association of disease severity with CG (heterozygous mutant) and CC (homozygous mutant) genotypes, i.e., an increased carriage rate of genotype CG and CC (homozygous mutant) was evident with the increase in the severity of CP, highlighting an increased susceptibility to CP due to this gene polymorphisms. Conclusion: PAI-1 genotype has a risk association with CP and alveolar bone loss severity in North-Indian population.